Translation of Federico García Lorca’s Poetry into Ukrainian (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
Tisevych A. Translation of Federico García Lorca’s Poetry into Ukrainian